Efficacy of Collagen Resorbable Membrane after Surgical Extraction of Impacted Mandibular Third Molar: Collagen Resorbable Membrane after Surgery of Impacted Mandibular Third Molar - Iqbal, Reham; Owais, Muhammad; Channa, Mansoor Ahmed; Punjabi, Suneel Kumar; Aslam, Muhammad Aqeel; Ayub, Tahera (Pakistan Journal of Health Sciences, 2024)
Impacted teeth, particularly mandibular third molars, can cause complications like pain, infection, and periodontal issues in adjacent teeth. Surgical management strategies, including the use of collagen-resorbable membranes, may improve healing and minimize postoperative complications.. Objectives: To evaluate the effectiveness of a collagen-resorbable membrane following surgical extraction of impacted mandibular third molars, focusing on pain severity, bone status, and periodontal ligament status adjacent to the second molar. Methods: The quasi-experimental study utilized a non-probability sampling technique for 6 months. Patients were equally divided into three groups: A (primary closure), B (secondary closure), and C (collagen membrane-based primary closure). Pain severity, bone status, and periodontal ligament status adjacent to the second molar were evaluated clinically and via post-operative radiographs postoperatively at the 2nd, 4th, 6th, and 12th weeks. Results: The study involved participants with an average age of 28.51 ± 7.53 years and an unequal gender distribution across all groups. Initially, Group C experienced higher moderate to severe pain levels. Group A had the longest surgery duration at 41.89 ± 14.10 minutes. By the second week of follow-up, pain significantly decreased in all groups, with no significant differences between them. By the fourth and sixth weeks, pain levels continued to decrease, with only mild pain observed in one patient each in Groups B and C. Conclusions:. There is no evidence to suggest that collagen resorbable membrane it is more effective than primary or secondary closure techniques